Measles second dose vaccine uptake and associated factors among under-five children in Jigjiga City, Somali Region, Eastern Ethiopia: a community-based cross-sectional study - Hafso Abdirahman Ibrahim; Abdi Wariyo; Elsai Mati Asefa; Abera Cheru; Arega Abebe Lonsako; Gebisa Dirirsa (Frontiers Media S.A., 2024)
BackgroundMeasles is one of the leading causes of under-five mortality and morbidity worldwide. Although the routine service for the second dose of the measles-containing vaccine (MCV2) was introduced in Ethiopia recently, there is a paucity of evidence regarding its coverage and the factors that hinder its uptake at both the local and national levels. Thus, this study aimed to assess the uptake of MCV2 and its associated factors among children aged between 15 and 36 months old in Jigjiga City, Somali Region, Ethiopia.MethodsA community-based cross-sectional study was conducted among 429 children aged between 15 and 36 months old with their mothers/caregivers in Jigjiga City from April 1 to May 1, 2023. A multistage sampling technique was used and data were collected by using structured interviewer-administered questionnaires. The collected data were entered into Epi-data version 3.2 and analyzed in a statistical package for the social sciences (SPSS) version 26. Bivariate and multivariable logistic regression analyses were performed to identify factors associated with the uptake of the measles second dose vaccine. An adjusted odds ratio with 95% CI were reported and statistical significance was declared at p < 0.05.ResultsThe coverage of MCV2 among children aged between 15 and 36 months was 21.4% (95% CI: 17.7, 25.2). The educational status of the mother (AOR = 3.154; 95% CI: 1.68, 5.93), place of delivery (AOR = 1.90; 95% CI: 1.08, 3.25), postnatal care visits of the mother (AOR = 2.40; 95% CI: 1.37, 4.22), time taken to reach a health facility (AOR = 2.67; 95% CI: 1.28, 5.57), and knowledge about child vaccination (AOR = 2.43; 95% CI: 1.45, 4.08) were factors significantly associated with the uptake of the measles second dose vaccine.ConclusionThe coverage of MCV2 in the study area was low compared to the national immunization targets. Educational status of the mother/caregivers, place of delivery, postnatal care visits of the mother, time to reach a health facility, and knowledge about vaccination of children were significantly associated with measles second dose vaccination. The focus should be given to improving the awareness of mothers on the importance of child vaccination to improve the uptake of measles second dose vaccine and reduce the burden of measles in the region.